(untitled) (Herald of Journalism, 2023)
In modern journalism theory, a comprehensive study of press for the entire history of our country has been conducted. In this sense, it is known that military journalism had a significant impact on society in different periods. The sphere of military journalism, which has become a full-fledged mass media of every era, is the core of a separate means of communication in military life, an integral part of the mass media. The aim of the research work is to comprehensively study and analyze the influence of patriotic education on the border troops during the Communist party period. In the education of modern military personnel in the fighting spirit, the problem of conducting informative work with the use of some ideological measures of the Soviet era is put forward. Compilation, analysis and comparison methods were used as the main ones. With the help of a differentiated approach, modern types of mass media and their influence on military personnel were studied. Scientific and practical significance of the research work: the author focuses on the role of military personnel’s education in the press and literature under the leadership of the Communist party. The activities of the press service of border guards in the spirit of patriotism under the Communist party were analyzed. The importance of the information flow in the education of military personnel in the national spirit was studied. In the course of the study, an idea about the influence of mass media on the personnel of all military force structures of the country through television, Internet, social networks, newspapers and magazines in order to reveal the ways of forming the spiritual values of soldiers is given. Comprehensively analyzed the fact that the information has its place in the life of the army. Komsomol youth and border guards reacted positively to the joint work on border protection. The results of the study showed that the “presence” of the Communist party in the press and literature during its leadership became the main direction of propaganda in the education of troops’ soldiers in the spirit of patriotism. Keywords: military journalism, education of border guards through mass media, patriotic education, discipline.